Overcoming Communicative Deadaptation of Speech Passive Children of Pre-School Age - Лариса Зданевич; Катерина Крутій (Психолінгвістика)
Introduction. The article analyzes the child’s speech concerning the individual peculiarities. It is about the formation of the communicative competence of the child. It is revealed that this process involves aspects: the acquisition of skills in the system-language and directly in the communicative spheres.